2017
DOI: 10.1016/j.cjtee.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neurofeedback on the short-term memory and continuous attention of patients with moderate traumatic brain injury: A preliminary randomized controlled clinical trial

Abstract: PurposeThere are some studies which showed neurofeedback therapy (NFT) can be effective in clients with traumatic brain injury (TBI) history. However, randomized controlled clinical trials are still needed for evaluation of this treatment as a standard option. This preliminary study was aimed to evaluate the effect of NFT on continuous attention (CA) and short-term memory (STM) of clients with moderate TBI using a randomized controlled clinical trial (RCT).MethodsIn this preliminary RCT, seventeen eligible pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Every brain damage causes conflicts with the so-called electric and chemical brain language, altering the space of prevailing networks and the action of neurotransmitters, which provoke a decline of the brain systems. Some studies confirmed that neurotherapy, also called neurofeedback therapy (NFT), can promote neuroplasticity [128]. NFT was shown to excite meaningful variants in structural and functional connectivity among young patients moderate TBI [127].…”
Section: Neuropsychological Rehabilitation (Nr) and Neurotherapymentioning
confidence: 99%
“…Every brain damage causes conflicts with the so-called electric and chemical brain language, altering the space of prevailing networks and the action of neurotransmitters, which provoke a decline of the brain systems. Some studies confirmed that neurotherapy, also called neurofeedback therapy (NFT), can promote neuroplasticity [128]. NFT was shown to excite meaningful variants in structural and functional connectivity among young patients moderate TBI [127].…”
Section: Neuropsychological Rehabilitation (Nr) and Neurotherapymentioning
confidence: 99%
“…Additionally, we highlight the effects of increasing fast waves , which is associated with increased cortical activation [19]. Likewise, the improvements in visual and verbal memory skills coincide with the findings of Rostami [20] that can be explained by changes in attentional control, which directly impact memory [16,21,22].…”
Section: Discussionmentioning
confidence: 92%
“…EEG neurofeedback is widely used to treat epilepsy [ 62 ]; it is also being administered in novel capacities to treat conditions such as fibromyalgia [ 63 ] or chronic prostatitis [ 64 ] and is commonly adopted in rehabilitation, for example, in patients with amyotrophic lateral sclerosis (ALS) [ 65 ], stroke [ 66 ], spinal cord [ 67 ], and traumatic brain injuries [ 68 , 69 ].…”
Section: Biofeedbackmentioning
confidence: 99%